2002
DOI: 10.1080/08039480252803927
|View full text |Cite
|
Sign up to set email alerts
|

Three cases of angel's trumpet tea-induced psychosis in adolescent substance abusers

Abstract: An increase of intoxications in persons using alkaloid-containing ornamental plants (mainly angel's trumpet) for their hallucinogenic effects and easy and cheap availability is registered. It is mainly adolescents who are experimenting with these plants. In addition to severe vegetative anticholinergic symptoms, the clinical picture is often dominated by a toxic psychosis with hallucinations, disturbances of orientation, and psychomotoric agitation, aggression, or anxiety. Three cases of severe psychotic pictu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 8 publications
1
29
0
5
Order By: Relevance
“…We showed (Barak and Weiner, 2007) that low doses of scopolamine (0.15, 0.5 mg/kg) led to LI disruption, and this was reversed by both typical and atypical APDs and by the acetylcholinesterase (AChE) inhibitor physostigmine, as found with muscarinic antagonist-induced pro-psychotic effects in humans (Brown et al, 2004 ;Gopel et al, 2002 ;Granacher and Baldessarini, 1975) and animals (Hohnadel et al, 2007 ;Jones et al, 2005). Based on this behavioural and pharmacological profile, we suggested that scopolamine-induced LI disruption might model the positive spectrum of the antimuscarinic syndrome.…”
Section: Introductionmentioning
confidence: 90%
“…We showed (Barak and Weiner, 2007) that low doses of scopolamine (0.15, 0.5 mg/kg) led to LI disruption, and this was reversed by both typical and atypical APDs and by the acetylcholinesterase (AChE) inhibitor physostigmine, as found with muscarinic antagonist-induced pro-psychotic effects in humans (Brown et al, 2004 ;Gopel et al, 2002 ;Granacher and Baldessarini, 1975) and animals (Hohnadel et al, 2007 ;Jones et al, 2005). Based on this behavioural and pharmacological profile, we suggested that scopolamine-induced LI disruption might model the positive spectrum of the antimuscarinic syndrome.…”
Section: Introductionmentioning
confidence: 90%
“…Anti-muscarinic psychosis is characterized by a number of schizophrenia-like symptoms, including attention and executive function difficulties, memory loss, multi-sensory hallucinations and delusions (see Barak, 2009, for a review). This drug-induced psychotic state can be treated with antipsychotic medications or acetylcholinesterase inhibitors, in addition to discontinuing the anti-muscarinic treatment that trigged the state (Göpel et al, 2002;Granacher and Baldessarini, 1975;Nogué et al, 1991). Similarly, acute administration of anti-muscarinic agents can also produce cognitive impairments amongst otherwise healthy human subjects that mimic the deficits documented amongst schizophrenia patients (e.g.…”
Section: The Muscarinic System and Schizophreniamentioning
confidence: 95%
“…Case reports exist of anticholinergic intoxication from moonflower seeds (Datura inoxia) (DeFrates et al 2005), nutmeg (Abernethy and Becker 1992), and angels trumpet (Brugmansia) (Isbister et al 2003;Gopel et al 2002).…”
Section: Drug Definitionmentioning
confidence: 98%